Unlocking success: the power of Resource-Based View / Salwa Muda and Musliha Musman - Muda, Salwa; Musman, Musliha (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The Resource-Based View (RBV) is a fundamental theory in the field of strategic management, originating from seminal works by Wernerfelt (1984) and Barney (1991). It garners interest from scholars across diverse management disciplines such as marketing, entrepreneurship, finance, international business, and human resource management. RBV posits that organizational resources have the potential to confer sustained competitive advantage, thereby influencing firm performance. Central to RBV is the notion that not all resources are equal. Some resources are more valuable, rare, difficult to imitate, or non-substitutable than others. These resources, when effectively utilized, can provide a firm with a sustainable competitive advantage that is difficult for competitors to replicate. At its core, RBV assumes heterogeneity among resource bundles and internal capabilities, which strategically differentiate firms from competitors (Barney, 1991; Wernerfelt, 1984). This implies that resources that meet these criteria are scarce and difficult to replicate, thereby providing firms with a lasting competitive edge.